The Grammar of Interaction : Epistemicity, Information Management and Discourse in Language Use - Susana Rodríguez Rosique; Jordi M. Antolí Martínez (John Benjamins Publishing Company, 2025)
This volume deals with the relations between grammar and interaction from different perspectives, with the aim of unraveling the way in which a language — through the different forms of discourse from which it emerges — reflects certain social and community-based schemas; that is, how language originates within the space shared by the speaker and the addressee(s). The first part (“Grammar and Interaction”) concerns how interaction may intervene in grammar; the second part (“The Grammar of Interaction”) approaches both notions and linguistic structures which are anchored in interaction while revolving around epistemicity, evidentiality and modality. The third part (“Interaction as a Model for Discourse”) concerns how certain constructions emerge from interaction and are further used to model discourse. Finally, the fourth and last part of the book (“Interaction as a Driver for Change”) focuses on how interaction may help to delimit linguistic categories.